The Church We Want: African Catholics Look to Vatican III. (Hekima Review, 2016)
The book "The Church We Want: African Catholic Look to Vatican III," is a product of a three-year theological research on the currents of the fiftieth anniversary of Vatican II. This book is organized into three parts. With a sub-title, “The Francis Effect and the Church in Africa” the essays in part one, take an incisive look at the phenomenon called “The Francis Effect” and the challenges it poses to the church in Africa and in the world. In part two, with a sub-title “Critique of Theological Methodology and Ecclesial Practice,” the focus is on a critique of the church in Africa and aspects of Christian identity, theological method, and ecclesial leadership. The third part of the book focuses on “A Church that Goes Forth with Boldness and Creativity.